EXOGENOUS PHOTOSENSITIVITY – Clinical Aspects and Responsible Agents - David Serra; Felicidade Santiago; Margarida Gonçalo; Américo Figueiredo (Journal of the Portuguese Society of Dermatology and Venereology, 2011)
Phototoxic and photoallergic reactions consist of sun-induced skin reactions in the presence of photoactive chemicals, applied directly on the skin or of systemic use. They have several distinct clinical presentations, including photocontact urticaria, eczema on sun exposed areas sometimes with erythema multiforme, exaggerated sunburn, phytophotodermatitis, pseudoporphyria, photo-onycholysis, dyschromia and lupus erythematosus. Furthermore, there is mounting evidence that exposure to photoactive chemicals contributes to cutaneous carcinogenesis. Besides their clinical heterogeneity, there is also a great diversity of causative agents, with striking geographical and temporal variations. The authors review the spectrum of clinical patterns and also major photosensitizers, including UV- -filters of sunscreens and cosmetics, vegetal furocoumarins and drugs (NSAIDs, antimicrobials, phenothiazines, amiodarone, among others).